Development of Augmented Reality-Based Game-Based Learning Integrated with Character Values to Improve Literacy and Problem-Solving Skills of Elementary School Students - Hardiyanti Sholeha, Herisa; Ismuwardani, Zakiyah; Guntur, Mochamad; Putri Febigyo, Anasya; Nur Syah Lukiyah, Nonih (UIN Sunan Kalijaga Yogyakarta, 2025)
Conventional learning practices are often ineffective in building values such as responsibility, honesty, cooperation, and discipline. Meanwhile, normative verbal moral approaches are also unable to touch on students' real experiences. Therefore, alternative learning media are needed that can integrate cognitive and affective learning simultaneously through a contextual and enjoyable approach. This research aims to develop game-based learning based on augmented reality integrated with character values as an alternative learning method that is more interactive, interesting, and easily accessible by teachers and students. The method used in this research is the ADDIE development method (analysis, design, development, implementation, and evaluation). Integrated with NIS, this research was conducted in elementary schools in the Cirebon district. The instruments include validation sheets, observations, literacy and problem-solving tests, and character value measurement questionnaires. The results showed that the augmented reality-based educational game developed met the eligibility criteria in terms of learning content, visual appearance, and integrity of character values. This can be seen from the results of literacy skills obtained, showing that the student's pretest score was 60, which increased to 85 in the posttest, an increase of 41.7%. And problem-solving skills were obtained by students' pretest score of 55, which increased to 80 in the posttest, with a rise of 45.5%. This study presents a novel integration of augmented reality with game-based learning and character Education at the elementary level, which has rarely been explored in previous research. Theoretically, it contributes to the intersection of digital pedagogy and frameworks for character development. Practically, it offers an innovative and empirically tested learning medium that supports literacy and problem-solving enhancement while fostering values such as responsibility, cooperation, and discipline. Thus, the results of game-based learning based on augmented reality prove that this medium is efficacious in improving students' literacy and problem-solving skills while strengthening the character of discipline, responsibility, and cooperation.